Contrast material and radiation dose reduction strategy for triple-rule-out cardiac CT angiography: feasibility study of non-ECG-gated low kVp scan of the whole chest following coronary CT angiography. (December 2014) - Kidoh, Masafumi; Nakaura, Takeshi; Nakamura, Shinichi; Namimoto, Tomohiro; Nozaki, Toshimitsu; Sakaino, Naritsugu; Harada, Kazunori; Yamashita, Yasuyuki
Background: Dedicated coronary computed tomography (CT) scan has been proven to be an accurate diagnostic modality in evaluating coronary artery disease. A second phase scan starting immediately after the coronary CT scan might enable visualization of the different vascular territories of the entire chest. Purpose: To investigate the feasibility of a contrast material and radiation dose reduction triple-rule-out (TRO) CT angiography (CTA) protocol with serial non-ECG-gated low kVp scan of the whole chest, which utilizes a recirculated contrast agent. Material and Methods: Thirty patients were scanned with the new TRO-CTA protocol; after the coronary scan with retrospective ECG-gating, non-ECG-gated whole-chest CTA was performed at 80 kVp to evaluate aortic arch (AAr) and pulmonary trunk (PT). Another 30 patients were scanned by our conventional TRO-CTA protocol at 120 kVp with retrospective ECG-gating. We compared the estimated effective dose (ED), contrast material (CM) dose, contrast-to-noise ratio (CNR) of the ascending aorta (AAo), and the rate of patients who could achieve adequate attenuation of the AAr and PT between the two protocols. Results: The total ED of the new TRO-CTA protocol was 29.6% lower than that of the conventional protocol ( P  < 0.01). The amount of CM used for the new TRO-CTA protocol was significantly lower than in the conventional protocol (60.1 ± 9.6 mL vs . 91.8 ± 22.6 mL, P  < 0.01). The CNR of the AAo was 30.2% higher with the new TRO-CTA protocol than with the conventional protocol ( P  < 0.01). There was no significant difference in the success rate of adequate attenuation of the AAr and PT between the two protocols ( P  > 0.05). Conclusion: The new TRO-CTA protocol can reduce the total dose of radiation and the contrast dose and yield adequate vascular enhancement compared with the conventional protocol.